ISOLATION AND IDENTIFICATION OF SOME PHYTOCHEMICAL COMPOUNDS FROM DIFFERENT PARTS OF IRIS NIGRICANS - Huwaitat, Sajee'; Al-Khateeb, Ekbal; Finjan, Samira (European Scientific Journal, ESJ, 2013)
ï»¿Iris genus (Iridaceae) is an elegant endemic plant species, and considered threatened to Jordan due to habitat degradation. Rhizomes of some Iris species contain flavonoids such as iridin, iriline A, irisone B. Iris leaves contain many flavonoids such as irilin, iristectorigenins, tectorigenin, and coumaronochromones. Iris flowers contain also flavonoids and proanthocyanidin while Iris nigricans have no previous studies conducted on leaves and flowers. In this study some phytochemical compounds were separated from different parts of Iris nigricans (rhizomes, leaves and flowers) by methanol. Isolation is carried out by using chromatographic technique and identified by ferric chloride reagent and UV light Î»max254-365nm. The phenolic composition of methanolic extracts of Iris nigricans obtained from rhizomes, leaves and flowers were elucidated by MS, 1H-NMR and 13C-NMR.